PERAWATAN ORTHODONTI GIGITAN TERBUKA ANTERIOR DENGAN POLA PERTUMBUHAN WAJAH HYPERDIVERGENT (LAPORAN KASUS) - Muslim Muslim; Erwin Siregar (Faculty of Dentistry, Universitas Indonesia, 2015)
Successful treatment of the adult patient with an open bite dental or skeletal pattern often presents a difficult challenge. The causes of open bite may be multifactorial in nature, there are specific diagnostic criteria that may allow for an orthodontic treatment modality incorporating extraction therapy with retraction of incisors. The intent of this article is to describe and demonstrate the extraction treatment of an open bite caused by a hyperdivergent facial pattern.